2016
DOI: 10.1186/s12963-016-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in prevalence and risk factors for hypertension in the Suriname Health Study: a cross sectional population study

Abstract: BackgroundLimited information is available about the prevalence, ethnic disparities, and risk factors of hypertension within developing countries. We used data from a nationwide study on non-communicable disease (NCD) risk factors to estimate, explore, and compare the prevalence of hypertension overall and in subgroups of risk factors among different ethnic groups in Suriname.MethodThe Suriname Health Study used the World Health Organization Steps design to select respondents with a stratified multistage clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
2
15
1
Order By: Relevance
“…The comprehensive, nation-wide Suriname Health Study on non-communicable diseases found an overall prevalence of hypertension of 26.2% [32]. This was in the range of values reported for many other developing countries [34] as well as the relatively large Surinamese diaspora in The Netherlands [35].…”
Section: Hypertensionmentioning
confidence: 64%
See 3 more Smart Citations
“…The comprehensive, nation-wide Suriname Health Study on non-communicable diseases found an overall prevalence of hypertension of 26.2% [32]. This was in the range of values reported for many other developing countries [34] as well as the relatively large Surinamese diaspora in The Netherlands [35].…”
Section: Hypertensionmentioning
confidence: 64%
“…These studies reported a higher incidence of prehypertension, hypertension, malignant hypertension, and related renal complications in participants from Afro-Surinamese and Hindustani descent compared to white individuals [35,[38][39][40]. These differences were tentatively explained by ethnic disparities in the perception of hypertension (supporting one of the findings of the Suriname Heath Study [32]), as well in drug adherence, blood pressure control, and/or insurance status [38,[40][41][42].…”
Section: Hypertensionmentioning
confidence: 85%
See 2 more Smart Citations
“…Both diabetes mellitus and hypertension were less prevalent than the national average for women (resp. 13% and 20%) [22][23]. The relatively high prevalence of Me TS found in both study groups coupled with the relatively low prevalence of hypertension and diabetes mellitus could be an indication that both these subpopulations are in epidemiological transition [2,24], though at different stages.…”
Section: Discussionmentioning
confidence: 81%